A facile green synthesis of silver nanoparticles decorated silica nanocomposites using mussel inspired polydopamine chemistry and assessment its catalytic activity. Issue 6 (December 2018) - Das, Tushar Kanti; Ganguly, Sayan; Bhawal, Poushali; Remanan, Sanjay; Ghosh, Sabyasachi; Das, Narayan Ch.
Graphical abstract: Highlights: Fabrication of catalytic AgNPs decorated hydrated silica (SPAgX) nanocomposites by mussel inspired dopamine chemistry. The SPAgX nanocomposites enhanced catalytic activity to reduction of 4-nitrophenol and potassium hexacyanoferrate (III). The SPAgX nanocomposites showed improved catalytic activity to degradation of Congo red. The separation method of SPAgX nanocomposites after catalytic process is very simple and highly scalable. The catalytic activity of SPAgX nanocomposites exhibited no apparent reduction after six cycles. Abstract: A facile process to synthesize polydopamine (PDA) coated silver nanoparticles (AgNPs) dispersed onto hydrated silica support has been reported here. The nanoparticles were evaluated by X-ray diffraction, FTIR and EDX study. The AgNPs size was found to be around ∼19.0 nm obtained from DLS, FESEM and TEM analysis. The UV–vis spectra of the prepared catalyst nanoparticles support the generation of AgNPs over PDA coated hydrated silica (SiO2 ) surface. The broadening at UV–vis spectra near ∼400 nm has a prominent evidence of AgNPs. The nanoparticles were employed as catalyst against 4-nitrophenol reduction, Congo red degradation and potassium hexacyanoferrate (III) reduction. The catalytic reaction was monitored in UV–vis spectrophotometer. The catalytic effect was observed as of minimal duration with respect to other reported values. The catalyst also has sufficient reusability upto six numbers of cycles without deterioration of its catalytic activity.